PPUPIK â€œSIPODEHâ€ Jahe Merah Instan Peluang Bisnis Mahasiswa Departemen Biologi - S. Syamsurizal; Sa`diatul Fuadiyah; Elsa Badriyya (Pelita Eksakta, 2023)
Ginger (Zingiber officinale) is an Indonesian spice plant which is widely used as traditional medicine. Another type of ginger that has more properties and a stronger spicy taste, namely red ginger. Red ginger is predicted to be able to inhibit the infection process of the SARS-CoV-2 virus in human host cells. Red ginger can increase the body's immunity, increase IgM levels and reduce the circulation of pro-inflammatory cytokines. The PPUPIK service team in collaboration with the HMJ Biology KWU Unit has developed the instant red ginger â€œSipodehâ€ product well. Currently we are expanding the marketing system. Some of the good practices that have been carried out are training the PPUPIK team to understand the basic concepts of marketing, studying marketing strategies, making simple bookkeeping. The results of this product marketing training were directly applied to various national scale activities by participating in bazaars at POMNAS at UNP. At the provincial level the "SIPODEH" team played an active role in the West Sumatra Malagak event sponsored by the West Sumatra regional government together with West Sumatra HIPMI. Participating in national and provincial scale activities succeeded in introducing "Sipodeh" instant red ginger well to consumers.